(3Jbhje GdehGQO GdeGOjI hGdHTQjI aj GdfTGW GdQjGVjs - (3ShQGf(B, (3cQje HGHGs ((3eUQ(B;(3eUQ(B:s (3OGQ GdhaGA dOjfG ddWHGYI hGdfTQ(B;(3eDSSI YGde GdQjGVI ddfTQ(B,s, 2023)
(3GdEWGQ GdYGe ddHMK, GdEWGQ GdfXQj hGdOQGSGJ GdSGHbI, GdfTGW GdQjGVj , CgejI GdfTGW GdQjGVj, eOjQjIGdfTGW GdQjGVj, CgOGa eOjQjI GdfTGW GdQjGVj, GdehXajf HeOjQjI GdfTGW GdQjGVj hGNJUGUGJge, CfhGYg GdCfTWI GdQjGVjI HeOjQjI GdfTGW GdQjGVj aj eMGaXI GQHjd HEbdje cQOSJGf, GdfTGW GdOGNdj, GdfTGW GdNGQLj, JYQja GdehGQO, GdehGQO GdQjGVjI, CgejI GdehGQO aj GdJQHjI GdQjGVjI, CgejI OQGSI GdehGQO GdQjGVjI, GdJbhje, GdJbhje aj GdeLGd GdQjGVj, CgejI GdJbhje, CgejI GdJbhje aj GdeLGd GdQjGVj, CgOGa GdJbhje, CSS GdJbhje, NUGFU GdJbhje, ELQGAGJ GdHMK, efgL GdHMK, eLJeY GdHMK, GNJjGQ eLJeY GdHMK, COhGJ GdHMK, GdeYGedGJ GdYdejI dJWHjb GSJeGQI GdESJHjGf, JWHjb COhGJ GdHMK, GdeYGdLGJ GdEMUGFjI(B.s
(3eQGLY U(B.305s
Keywords: (3GdQjGVI GdHOfjIs; (3GdfhGOj GdQjGVjIs